Issi saaneq gen. Et sp. nov.—A new sauropodomorph dinosaur from the late triassic (norian) of jameson land, central east greenland - Beccari, Victor; Mateus, Octávio; Wings, Oliver; Milàn, Jesper; Clemmensen, Lars B. (Diversity, 2021)
UIDB/04035/2020 The Late Triassic (Norian) outcrops of the Malmros Klint Formation, Jameson Land (Green-land) have yielded numerous specimens of non-sauropod sauropodomorphs. Relevant fossils were briefly reported in 1994 and were assigned to Plateosaurus trossingensis. However, continuous new findings of early non-sauropod sauropodomorphs around the globe facilitate comparisons and allow us to now revise this material. Here, the non-sauropod sauropodomorph Issi saaneq gen. et sp. nov. is described based on two almost complete and articulated skulls. The two skulls represent a middle-stage juvenile and a late-stage juvenile or subadult. Issi saaneq differs from all other sauropodomorphs by several unique traits: (1) a small foramen at the medial surface of the premaxilla; (2) an anteropos-teriorly elongated dorsoposterior process of the squamosal; (3) a relatively high quadrate relative to rostrum height; (4) a well-developed posterodorsal process of the articular. These features cannot be explained by taphonomy, ontogeny, or intraspecific variation. Issi saaneq shows affinities to Brazilian plateosaurids and the European Plateosaurus, being recovered as the sister clade of the latter in our phylogenetic analysis. It is the northernmost record of a Late Triassic sauropodomorph, and a new dinosaur species erected for Greenland. Issi saaneq broadens our knowledge about the evolution of plateosaurid sauropodomorphs. publishersversion published